PENGEMBANGAN KAIN TENUN CEPUK SEBAGAI BAGIAN PARIWISATA BUDAYA BERKELANJUTAN DI NUSA PENIDA - Firlie Lanovia Amir (Jurnal Ilmiah Hospitality Management, 2017)
Bali has a variety of tourism potentials including cultural tourism either in the form of products or exotic craft. One fairly well-known cultural productis woven fabrics (Kain Tenun), such as Kain Tenun Cepuk that exist in the area of Nusa Penida. The existence and uniqueness of the woven fabric is expected to help increasing tourism in the island, as well as increasing the income of both Bali tourism sector or specifically the people of Nusa Penida. Thus the present study was made to assess the potential Woven fabric tube Tanglad, Nusa Penida, as well as determine strategies and programs that can be done to develop the potential of the woven fabric tube Tanglad as a means of developing cultural tourism. This study is using a qualitative descriptive approach to measure the variables involved, and SWOT matric to explain and define the data in the formulation of strategies and programs. The data obtained several factors that determine the potential development of the Kain Tenun Cepuk, which is categorize as internal and external factors, in which successfully formulated four strategiesand programsthat can be developed, covering SO strategies (developingKain Tenun Cepuk and the surrounding areas), ST (developing cultural tourism in Tanglad and Nusa Penida), WO (dealing with right promotion issue), and WT (related to human resource development). The research is expected to be referencedto number of policies that can be taken by local government to develop tourism in Tanglad, Nusa Penida, as well as for the community to be able to develop the potential of the Kain Tenun Cepuk better.